2019
DOI: 10.5267/j.uscm.2018.7.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimal decision problem in a three-level closed-loop supply chain with risk-averse players under demand uncertainty

Abstract: In this paper, a stochastic model of a closed-loop supply chain (CLSC) with one risk-averse manufacturer, one risk-averse retailer and one risk-averse third party is developed. To analyze how the members make decisions about wholesale price, collection rate, retail price and sales effort under different decision-making structures, the optimal decision problem under uncertain price and sales effort-dependent demand is studied through development of four game theoretical models. The equilibrium results between v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Yoo (2014) considered a supply chain with a risk‐averse supplier and studied the firms' product quality and return strategy. Alamdar, Rabbani, and Heydari (2019) addressed the optimal decisions in a supply chain consisting of a risk‐averse manufacturer, a risk‐averse retailer, and a risk‐averse third party. These works mainly focus on how the firms' risk aversion affects the other parties' decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yoo (2014) considered a supply chain with a risk‐averse supplier and studied the firms' product quality and return strategy. Alamdar, Rabbani, and Heydari (2019) addressed the optimal decisions in a supply chain consisting of a risk‐averse manufacturer, a risk‐averse retailer, and a risk‐averse third party. These works mainly focus on how the firms' risk aversion affects the other parties' decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 26 Alamdar et al investigated the choice of pricing and collection strategies in a closed-loop supply chain with a single risk-averse manufacturer, retailer, and third party under uncertain demand. 27 Abbey et al examined the influence of risk preferences on consumers’ willingness to pay (WTP) for remanufactured products and found that the WTP data can be reasonably explained by a typical utility model with risk aversion and that ambiguity aversion does not play a significant role in consumers’ choices. 28 Deng examined how consumers’ risk aversion affects the choice of remanufacturing models and the environmental performance of the supply chain and assessed the environmental effects of each model and examined the best choices and profits made by supply chain participants under various models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The risk-aversion behavior of supply chain members affects the decision-making of the supply chain system. Researchers have considered risk-averse supply chain pricing strategies (Liu et al, 2016); other researchers investigate the impact of risk aversion on pricing and supply chain coordination from the perspectives of demand uncertainty and asymmetric information (Xiao and Yang, 2008;Li et al, 2017;Alamdar et al, 2019;Bai et al, 2020).…”
Section: Related Papermentioning
confidence: 99%